2017
DOI: 10.1063/1.4984259
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for optimizing composite towers for use on floating wind turbines

Abstract: A methodology for the design and optimization of a composite wind turbine tower for use on a floating offshore platform is presented. A composite turbine tower on a floating offshore platform not only has the potential to reduce maintenance and upkeep costs associated with the use of steel offshore but also has potential to reduce the tower mass and subsequently the support platform mass. The optimization problem is formulated to obtain a turbine tower that meets all strength and serviceability criteria and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…It is possible that even with additional optimization composites may remain an unsuitable for the tower of a standardized "soft-stiff" OWT design due to secondary effects on the foundation. Composite tower concepts that mitigate the flexible behavior, such as the C-Tower's "soft-soft" design [3], concepts that use active-pitch control to minimize displacement via blade drag, or concepts that use the lower mass of a tower to reduce foundation size and cost such as VolturnUS [2] remain viable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that even with additional optimization composites may remain an unsuitable for the tower of a standardized "soft-stiff" OWT design due to secondary effects on the foundation. Composite tower concepts that mitigate the flexible behavior, such as the C-Tower's "soft-soft" design [3], concepts that use active-pitch control to minimize displacement via blade drag, or concepts that use the lower mass of a tower to reduce foundation size and cost such as VolturnUS [2] remain viable.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing size of structures reduces the benefits of steel as selfweight becomes a design driver in the traditionally steel dominated offshore industry. Composite towers are being considered [2,3] as alternatives for offshore wind turbines (OWT). Composites consisting of glass fibers in an epoxy resin matrix may provide benefits such as better fatigue performance and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The work of Zuo et al [16] used multiple tuned mass dampers to control vibrations from the fundamental and higher modes of an OWT tower, under combined wind, sea wave, and earthquake excitations. The work of Young et al [17] presented an optimal design for a floating wind turbine tower, while the steel tower was compared to the composite materials tower, and the results demonstrated that the composite can significantly reduce the tower mass. Abhinav and Saha [18] investigated the response of a jacket supporting an OWT with the Define SSI, where the effect of the SSI became predominant for an OWT in loose sands.…”
Section: Introductionmentioning
confidence: 99%